PENGARUH PENERAPAN STRATEGI KELOMPOK ACAK (SCRAMBLED GROUPS) TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII SMPN 38 SIJUNJUNG TAHUN PELAJARAN 2012/2013 - Silvina, Rini; Sumarmin, Ramadhan; Maizeli, Annika (Pendidikan Biologi, 2013)
ABSTRACTThe lack of interest and students motivation to study biology lead them to get low achievement. This case can see from the students average learning outcomes of biology at SMPN 38 Sijunjung grade seven which gotten score below the Minimum Completeness Criteria (MCC). One of reason is the lack variation of the strategy by the teacher, therefore learning process is monotonous. To solve this problem need to apply the strategy that can make students be active and get motivation in learning process. This research has purpose to know the effect the by using implementation Scrambled Groups strategy on students learning outcomes of biology at SMPN 38 Sijunjung grade seven academic year 2012/2013. This research is experiment. The population is students grade seven at SMPN 38 Sijunjung that listed in the academic year 2012/2013 which consists of two classes. Both of these classes were sampled (saturated sampling), to determine experimental class and control class conducted the draw, which was chosen to be experimental is class VII1 and control class is VII2. The instrument used was a test. Student learning outcomes and obtained an average value of 77,23 experimental class and control class 67,72. Data analysis was to test the similarity of the two premises mean t-test at the 0.05 significance level. Based on the analysis of data obtained the price 2,03 tcount 1.67 ttable. This means that tcount > ttable, therefore the hypothesis is accepted. Therefore the implementation of Scrambled Groups strategy can improve the learning outcomes of students in biology at SMPN 38 Sijunjung grade seven academic year 2012/2013.